Legal Certainty Regarding the Execution of State Administrative Court Decisions That Have Permanent Legal Force - Asep Muhidin (al-Afkar, Journal For Islamic Studies, 2023)
As a rule of law country, Indonesia has regulated the settlement of administrative disputes between legal entities and the government, individuals and the government, and employees and the government which are examined, resolved and decided by the State Administrative Court (PTUN). PTUN decisions that have permanent legal force (inkracht van gewijsde) must be implemented by the party ordered in the decision. However, there are still many government officials who do not implement PTUN decisions that have permanent legal force. invitation. Based on Article 116 of Law Number 51 of 2009 concerning the Second Amendment to Law Number 5 of 1986 concerning the State Administrative Court (UU PRATUN), the Head of the State Administrative Court only submits a letter to the President as the holder of the highest government power to order the official to implement the court's decision, and to the people's representative institutions to carry out the oversight function. This method is not effective because the actualization of the President and the DPR (people's representatives) has not been found in writing to warn officials who do not comply with the law, causing legal uncertainty. This study aims to find out what obstacles that lead to disobedience or non-implementation of PTUN decisions that have permanent legal force by government officials and what efforts must be made because there is no special field as the executor of the forced execution of PTUN decisions. This research uses a descriptive analysis method and a normative juridical approach. From the results of the research, it was found that the government must have the courage to make breakthroughs in the institutions of the State Administrative Court so that the decisions of PTUN judges have value and are respected, namely making rules regarding the establishment of special bodies or fields that have duties and functions as executors of PTUN decisions to create and realize the principle of legal certainty in the rule of law for all citizens who are in dispute so that in the future the PTUN decision will no longer be branded as a toothless tiger because the implementation of forced executions by the judiciary and other state security institutions cannot yet be implemented because there are no laws and regulations that strictly regulate the execution of forced executions of Administrative Court Decisions State Enterprises by whom and in what procedures